Setting up a pragmatic clinical trial in a low-resource setting: A qualitative assessment of GoLBeT, a trial of podoconiosis management in Northern Ethiopia. - Astrid C Erber; Victoria Ewing; Mark Turner; Meseret Molla; Gharib Murbe; Fikre Enquoselassie; Gail Davey; Trudie Lang (Public Library of Science (PLoS), 2021)
Background Clinical trials are often perceived as being expensive, difficult and beyond the capacity of healthcare workers in low-resource settings. However, in order to improve healthcare coverage, the World Health Organization (WHO) World Health Report 2013 stated that all countries need to become generators as well as recipients of data. This study is a methodological examination of the steps and processes involved in setting up the Gojjam Lymphoedema Best Practice Trial (GoLBeT; ISRCTN67805210), a highly pragmatic clinical trial conducted in northern Ethiopia. Challenges to the trial and strategies used to deal with them were explored, together with the reasons for delays. Methodology and principal findings Qualitative research methods were used to analyse emails and reports from the period between trial inception and recruitment. This analysis was complemented by interviews with key informants from the trial operational team. The Global Health Research Process Map was used as a framework against which to compare the steps involved in setting up the trial. A mini-group discussion was conducted with the trial operational team after study completion for reflection and further recommendations. This study showed that the key areas of difficulty in setting up and planning this trial were: the study design, that is, deciding on the study endpoint, where and how best to measure it, and assuring statistical power; recruitment and appropriate training of staff; planning for data quality; and gaining regulatory approvals. Collaboration, for example with statisticians, the trial steering committee, the study monitors, and members of the local community was essential to successfully setting up the trial. Conclusions and significance Lessons learnt from this trial might guide others planning pragmatic trials in settings where research is not common, allowing them to anticipate possible challenges and address them through trial design, planning and operational delivery. We also hope that this example might encourage similar pragmatic studies to be undertaken. Such studies are rarely undertaken or locally led, but are an accessible and efficient way to drive improved outcomes in public health.